Impact of Taxes on the Financial Statements prepared under IFRS - Tydlačková, Ivana; Vašek, Libor, 1978-; Zárybnická Žárová, Marcela, 1959-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
The master's thesis focuses on the impact taxes have on the financial statements prepared under IFRS. The theoretical part of the thesis provides a theoretical background of direct and indirect taxes from different points of view. The brief characteristic of each tax according to a tax theory is completed with the current development and the accounting for the tax. In practical part of the thesis the case of real entity reporting under IFRS as well as under the Czech national legislation is discussed. Financial Statements prepared by the chosen entity, České dráhy, a.s., are assessed in relation to the taxation and its predictive ability.
Vedoucí práce: Libor Vašek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; finance and accounting for common europe [obor dipl. práce]